(untitled) - Great Britain; Law Commission (London, 1998)
This book inclues many parts: land registration today - a critical overviewdefinitions and concepts, overriding interests, overriding interests,...
Keywords: Land titles,Quyền sử dụng đất; Registration and transfer,Đăng ký và chuyển giao; England; Anh